Approaches to characterize chromatin subcompartment organization in the cell nucleus - Weinmann, Robin; Frank, Lukas; Rippe, Karsten (Current opinion in structural biology, 2023)
The mechanism of self-organization of chromatin subcompartments on the 0.1-1 μm scale and their impact on genome-associated activities has long been a key aspect of research on nuclear organization. Understanding the underlying structure-function relationship, however, remains challenging due to the complex hierarchical structure of chromatin and the polymorphic organization of subcompartments that assemble around it. Towards this goal, approaches to measure local properties and compositional dynamics of chromatin in its endogenous cellular environment are instrumental. Here, we discuss recent advancements in studying these features and their functional implications in protein and RNA enrichment and genome accessibility.
Online veröffentlicht: 16. September 2023
Gesehen am 21.11.2023